Applications of anisotropic one‐step leapfrog HIE‐FDTD method in microwave circuit and antenna. Issue 5 (23rd January 2020) - Zhang, Kanglong; Wang, Lu; Wang, Mengjun; Zheng, Hongxing; Li, Erping
Abstract: To verify the effect of artificial anisotropy parameters in one‐step leapfrog hybrid implicit‐explicit finite‐difference time‐domain (FDTD) method, we calculated several microwave components with different characteristics. Introduced auxiliary field variable can reduce the program difficulty and improve the computational efficiency without additional computational time and memory cost. Analyses of the numerical results are proved that the calculation time is reduced to about one‐sixth compared to the traditional FDTD method for the same example simulated. The memory cost and relative error are remained at a good level. The numerical experiments for microwave circuit and antenna have been well demonstrated the method available.